ANALISIS PENGARUH KAIZEN TERHADAP KINERJA KARYAWAN PT FUMAKILLA INDONESIA UNIT BANJARMASIN - Muhammad Iman Ramadhan; Ahmad Alim Bachri; Maya Sari Dewi (JWM (JURNAL WAWASAN MANAJEMEN), 2014)
This research aimed to identify and analyze the influence of kaizen which consist of seiri (X1), seiton (X2), seiso (X3), seikestu (X4), and shitsuke (X5) as independent variables either simultaneously or partially to the employees’ performance (Y) as dependent variable at PT Fumakilla Indonesia, Banjarmasin unit. The instrument used in this research was questionnaire and then it distributed to all production employees (105 people) at PT Fumakilla Indonesia, Banjarmasin Unit based on a sample census. The variable measured by using Likert Scale from 1 to 5. Multiple linear regression analysis also used to determine the effect of independent variables, namely seiri (X1), seiton (X2), seiso (X3), seikestu (X4), and shitsuke (X5) to the dependent variable, that is employees’ performance (Y) simultaneously or partially. The results indicate that kaizen which consist of seiri (X1), seiton (X2), seiso (X3), seikestu (X4), and shitsuke (X5) simultaneously affect the employees’ performance (Y). Whereas, as partially, only seiri (X1), seiton (X2), and seiso (X3) significantly have influence to the employees’ performance, whereas seikestu (X4) and shitsuke (X5) have no significant influence.